Modern control engineering - Ogata, Katsuhiko (Prentice Hall, 1997)
"Comprehensive treatment of the analysis and design of continuous-time control systems" Partial contents : The Laplace transform ; Mathematical modelling of dynamic system ; Transient-response analysis ; Root-locus analysis ; Frequency response analysis ; PID controls and introduction to robust control ; Control systems in state space ; Liapunov stability analysis and quadratic optimal control.